Philosophy, mysticism, and the political : essays on Dante - Cacciari, Massimo (State University of New York Press, 2021)
Nine masterful essays on Dante's Divine Comedy and his political theology by one of today's leading Italian philosophers.
Keywords: Dante Alighieri, -- 1265-1321. -- Divina commedia.; Dante Alighieri, -- 1265-1321 -- Political and social views.; Cacciari, Massimo -- Translations into English.; Cacciari, Massimo; Dante Alighieri, -- 1265-1321; Divina commedia (Dante Alighieri); Political and social views; Translations; Literary criticism; Essays; Essays.; Literary criticism.; Critiques littéraires.